AGRICULTURAL LAND CONSOLIDATION PLANNING STRATEGY USING SWOT ANALYSIS (Study at Sitinjo Village, Sitinjo District, Dairi Regency) - Feby Milanie; Ruri Prihatini Lubis; Jimmy Karendi; Wirdatul Akmal; Novi Armen; Roldes Ricardo; Inas Suha Azzahra (Bulletin of Engineering Science, Technology and Industry, 2025)
This study aims to analyze the strengths, weaknesses, opportunities, and threats (SWOT) in the implementation of the Land Consolidation program in Sitinjo Village, Sitinjo District, Dairi Regency. The research methodology uses a qualitative descriptive approach with the SWOT method based on the 2021 Land Consolidation Planning Technical Material document from the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Regional Office of North Sumatra Province. The results of the analysis show that the main strength factors are the potential for productive agricultural land and community support, while the main weakness is limited land accessibility. Opportunities stem from government policy support and the potential for community economic improvement, while threats include the risk of land conflicts and spatial planning changes. The recommended strategy is to optimize land access infrastructure and increase community participation in planning and implementation.